Obesity Exacerbates Coxsackievirus Infection via Lipid-Induced Mitochondrial Reactive Oxygen Species Generation - Kim, Seong Ryeol; Song, Jae Hyoung; Ahn, Jae Hee; Jeong, Myeong Seon; Yang, Yoon Mee; Cho, Jaewon; Jeong, Jae Hyeon; Cha, Younggil; Kim, Kil Nam; Kim, Hong Pyo; Chang, Sun Young; Ko, Hyun Jeong (Immune Network, 2022)
Coxsackievirus B3 (CVB3) infection causes acute pancreatitis and myocarditis. However, its pathophysiological mechanism is unclear. Here, we investigated how lipid metabolism is associated with exacerbation of CVB3 pathology using high-fat diet (HFD)-induced obese mice. Mice were intraperitoneally inoculated with 1×106 pfu/mouse of CVB3 after being fed a control or HFD to induce obesity. Mice were treated with mitoquinone (MitoQ) to reduce the level of mitochondrial ROS (mtROS). In obese mice, lipotoxicity of white adipose tissue-induced inflammation caused increased replication of CVB3 and mortality. The coxsackievirus adenovirus receptor increased under obese conditions, facilitating CVB3 replication in vitro. However, lipid-treated cells with receptor-specific inhibitors did not reduce CVB3 replication. In addition, lipid treatment increased mitochondria-derived vesicle formation and the number of multivesicular bodies. Alternatively, we found that inhibition of lipid-induced mtROS decreased viral replication. Notably, HFD-fed mice were more susceptible to CVB3-induced mortality in association with increased levels of CVB3 replication in adipose tissue, which was ameliorated by administration of the mtROS inhibitor, MitoQ. These results suggest that mtROS inhibitors can be used as potential treatments for CVB3 infection.
Keywords: Coxsackievirus B3; Lipid metabolism; Mitochondria; Mitoquinone; Obesity; Reactive oxygen species